Pricing of Initial Audit Engagements by Large and Small Audit Firms* - Ghosh, Aloke; Lustgarten, Steven (Contemporary Accounting Research, 2006)
We investigate the extent to which auditors of U.S. companies reduce fees on initial audit engagements (“fee discounting”). We hypothesize that rivalries among sellers, in terms of client turnover and price competition, are more intense among small audit firms. The data support this hypothesis. New clients account for 34 percent of all clients for small audit firms, but only 9 percent of all clients for large audit firms. We theorize that differences in client turnover rates between large and small audit firms can be explained by the market structure of the audit industry, which consists of an oligopolistic segment dominated by a few large audit firms and an atomistic segment composed of many small audit firms. We further hypothesize and confirm that fee discounting is more extensive in the atomistic sector, and our results confirm this hypothesis. Our analysis of audit fee changes indicates that clients who switch auditors within the atomistic sector receive on average a discount of 24 percent over the prior auditor's fee. However, clients who switch auditors within the oligopolistic sector receive on average a discount of only 4 percent. Given that price competition is known to be less intense in oligopolistic markets than in atomistic markets, we believe that market structure theory can explain why fee discounting is lower when larger audit firms compete for clients.